2008
DOI: 10.1177/003335490812300613
|View full text |Cite
|
Sign up to set email alerts
|

Impact of School-Based Health Centers on Students with Mental Health Problems

Abstract: SYNOPSISObjectives. School-based health centers (SBHCs) play an increasingly major role in providing mental health services for students. This study evaluated the impact of SBHCs on mental health-care services and psychosocial healthrelated quality of life (HRQOL). 50.006, p50.9361) for urban and rural non-SBHC schools, respectively. Using data from 109 students with mental health problems based on Medicaid claims, the study found SBHC students had significantly lower total health-care costs (F55.524, p50.005)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 32 publications
1
56
0
1
Order By: Relevance
“…Users of SBHC were also often described as exhibiting more high risk behaviors including unprotected sexual intercourse, substance usage, and suicidal behavior than non-users of services [12,15,17,29,38,41,43,47]. Adolescents exposed to SBHC received more mental health services compared with those in schools without SBHC and there appeared to be a cost efficiency saving comparing them to those not exposed [35,46]. It appears therefore, that SBHC can reach adolescents with the greatest level of need.…”
Section: Discussionmentioning
confidence: 99%
“…Users of SBHC were also often described as exhibiting more high risk behaviors including unprotected sexual intercourse, substance usage, and suicidal behavior than non-users of services [12,15,17,29,38,41,43,47]. Adolescents exposed to SBHC received more mental health services compared with those in schools without SBHC and there appeared to be a cost efficiency saving comparing them to those not exposed [35,46]. It appears therefore, that SBHC can reach adolescents with the greatest level of need.…”
Section: Discussionmentioning
confidence: 99%
“…3 Students from disadvantaged backgrounds in schools with an SBHC are frequently found to have increased access to health care, including mental health services. 36,4648 Across all age-groups, general health examinations are among the most common reason for visiting an SBHC. 5,9,34,47,49 …”
Section: Sbhcs and Health And Social Outcomesmentioning
confidence: 99%
“…Other evaluations of SBHCs’ behavioral health impact have reported lower rates of suicidality and depression, increased physical activity, increased hormonal contraception use, increased likelihood of having been screened for a STI including HIV, lower pregnancy rates and, among teen parents who used SBHCs, higher newborn birth weights [[12], [13], [14], [15], [16], [17], [18], [19], [20], [21]]. Some studies have also found that access to SBHCs is associated with positive academic outcomes, including increased attendance and grade point average and reduced rate of dropout [[22], [23], [24]].…”
Section: Sbhc Research: Scope Of the Evidence Basementioning
confidence: 99%